The Effect of Freezing Shopee Paylater Accounts on BI Checking: Case Study on INSAN Binjai Students Stambuk 2021-2024 - Fadila, Ilham; Harahap, Raja Sakti Putra (Journal of Management Sains (JMS), 2025)
Aim for this research is to find out the regulation of OJK (Financial Services Authority) used by OJK and legal protection for prospective Bank Customers for credit rejection cause BI Checking in the shopee application. Method of this research is normative legal research with statute and conceptual approach. Based on result, that BI Checking is used as a tool to check the history of default/bad credit against a prospective customer at a financial institution, both Bank and non-Bank financial institutions. BI Checking is also included as a checking tool in payments using the shopee application, customers who have had a history of default on the shopee application are considered to have a history of default which causes prospective customers to be rejected when applying for credit at the Bank even though the bill has been paid off, the lack of certainty of the customer’s name clearance period must be clarified so that customers when applying for credit at other financial institutions are not constrained.